Tuning of the electronic properties of H‐passivated armchair graphene nanoribbons by mild border oxidation: Theoretical study on periodic models. Issue 17 (1st June 2016) - Ghigo, Giovanni; Maranzana, Andrea; Tonachini, Glauco
Abstract : We report the results of a DFT study of the electronic properties, intended as highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies, of periodic models of H‐passivated armchair graphene nanoribbons ( a ‐GNRs) as that synthetized by bottom‐up technique, functionalized by vicinal dialdehydic groups. This material can be obtained by border oxidation in mild and easy to control conditions with 1 Δg O2 as we reported in our previous paper (Ghigo et al., ChemPhysChem 2015, 16, 3030). The calculations show that the two models of border oxidized a ‐GNRs (model A, 0.98 nm and model B, 1.35 nm wide) present LUMO and HOMO energies lowered by an extend roughly linearly dependent on the amount of oxygen chemically bound. The frontier orbital energy variations dependence on the % wt of oxygen bound are, for model A: −0.12 eV for the LUMO and −0.05 eV for the HOMO; for model B: −0.15 eV (HOMO) and −0.06 eV (LUMO). © 2016 Wiley Periodicals, Inc. Abstract : Tuning the energies of frontier orbitals of graphene nanoribbons (GNRs) is important because the HOMO‐LUMO gap affects the electronic and optic properties of such materials, and as such their applicability for electronic devices. First‐principles calculations suggest that frontier orbital energies of armchair GNRs can be tuned through dialdehydic functionalization by oxidation in mild conditions.